Welfare State Transformations
XIV, 264 p.
Keywords: This edited volume provides new empirical evidence of far-reaching changes to welfare states globally, which have changed the boundaries of the 'public' and 'private' domain within the mixed economies of welfare. Various modes of policy intervention are investigated, providing a nuanced account of reforms in the past decade.